Simulasi Kendali Altitude Quadcopter Parrot Mambo menggunakan Linearisasi Fungsi Alih dan PID - Tan Varian Kashira; Eko Setiawan; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Unmanned Aerial Vehicle is one type of drone that has developed rapidly. UAV has a lot of potential that can be explored, both for personal needs such as a toys to professional needs such as military aid. As electronics and computer science develop, in-depth research on quadcopters is carried out. One of the studies that continues being developed is control system. Quadcopters needs control system in order to maneuver according to the purpose. The control system in a quadcopter includes many things, such as attitude and altitude control systems. This research is a simulation of the Parrot Mambo altitude control system using linearized transfer function and PID (Proportional Integral Derivative) by simplifying the Parrot Mambo block model in order to apply the PID tuning results into the Parrot Mambo nonlinear system. According to the results of the simulation, the application of the transfer function and PID in 5 levels of height test reduced overshoot to 0%, increased rise time to 4.216 seconds, and increased settling time to 3,468 seconds. Testing with 5 different masses with transfer and PID functions, was able to reduce overshoot to 0%, increase in rise time by 4.001 seconds, and increase in settling time by 4.216 seconds. In testing the response of the original blocks and simplified blocks, the results were identical results and did not affect the basic function of the system itself. This can be seen in the difference from the overshoot response which is 0.01%, the settling time is 0.1 seconds, and the rise time is 0.005 seconds.